Studi Literatur: Analisis Tentang Pengaruh Beban Pajak Terhadap Manajemen Laba - Wulandari, Desy; Anggawijaya, Anthony; Meiden, Carmel (Jurnal Riset Akuntansi dan Manajemen Malahayati (JRAMM), 2023)
This study aims to explain the effect of the tax burden on earnings management. The framework built is the effect of tax burden and tax planning can affect earnings management incompanies. This research method uses a systematic literatur study method and the application of PoP (Publish or Perish). Keywords such as “earnings management”, “tax espense”, and “tax planning” are used in research to find articles related to research problems. The object of this research was obtained as many as 31 articles taking  into account certain criteria, with the period from 3017 to 2022. The results of the research show that the tax burden for companies can reduce the amount of profits. Researchers also found that tax burden and tax planning can affect earnings management. This causes management to carry out earnings management through tax planning and tax burden on the financial statements.